Surgical Synechiolysis of Iridocapsular Adhesion and Sulcus Placement of a Rigid Intraocular Lens on an Oversized Residual Capsular Rim - Jiao Lyu; Qi Zhang; Haiying Jin; Tingyi Liang; Jili Chen; Peiquan Zhao (Journal of Ophthalmology)
Purpose. To report the surgical outcomes of surgical synechiolysis of iridocapsular adhesion and sulcus placement of a polymethyl methacrylate scleral-sutured intraocular lens (IOL) in aphakic eyes with an oversized residual capsular rim. Methods. Eight aphakic eyes from eight consecutive patients were studied retrospectively. Synechiolysis was performed to maximally expose the residual capsulorhexis. Then, the rigid IOL was placed on the preserved capsulorhexis into the ciliary sulcus. Results. Synechiolysis of iridocapsular adhesion was achieved in all eight eyes intraoperatively. Six eyes had extensive dissection to facilitate IOL sulcus placement. Consequently, seven of the eight eyes had the IOL secured by the residual capsulorhexis, and the other eye had the IOL haptics supported by the narrow residual capsular rim. A visual acuity of 0.25 or above was achieved in four of eight patients, and a well-centered IOL was observed in seven of the eight eyes 26 to 53 months after surgery. A mild IOL decentration was detected in the eye whose capsular rim was not securing the IOL optic. Conclusions. A large-optic and rigid IOL in the sulcus is a feasible alternative when a sulcus-based IOL is considered for aphakic eyes with an oversized residual capsulorhexis. A preserved capsulorhexis after sufficient synechiolysis, which can secure the IOL optic intraoperatively, may yield better stability of the IOL position.